2015
DOI: 10.1371/journal.pone.0123324
|View full text |Cite|
|
Sign up to set email alerts
|

Colostrum of Healthy Slovenian Mothers: Microbiota Composition and Bacteriocin Gene Prevalence

Abstract: Microbial communities inhabiting the breast milk microenvironment are essential in supporting mammary gland health in lactating women and in providing gut-colonizing bacterial 'inoculum' for their infants’ gastro-intestinal development. Bacterial DNA was extracted from colostrum samples of 45 healthy Slovenian mothers. Characteristics of the communities in the samples were assessed by polymerase chain reaction (PCR) coupled with denaturing gradient gel electrophoresis (DGGE) and by quantitative real-time PCR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
3
19
0
2
Order By: Relevance
“…Our data are generally similar to those previously published by others. For example, the microbial composition of colostrum we collected on day 2 postpartum was similar to that described by Obermajer et al ( 29 ). Unlike what was reported by Cabrera-Rubio et al ( 30 ), however, Weisella and Leuconostoc were only present in very low relative abundances (0.01% and 0.03%, respectively) in one colostrum sample we collected.…”
Section: Discussionsupporting
confidence: 74%
“…Our data are generally similar to those previously published by others. For example, the microbial composition of colostrum we collected on day 2 postpartum was similar to that described by Obermajer et al ( 29 ). Unlike what was reported by Cabrera-Rubio et al ( 30 ), however, Weisella and Leuconostoc were only present in very low relative abundances (0.01% and 0.03%, respectively) in one colostrum sample we collected.…”
Section: Discussionsupporting
confidence: 74%
“…The human milk microbiota may be involved in the development of infant innate immunity and serve as a functional link between maternal and infant gut microbiota 8 , 33 . This relationship is multifactorial and dependent on many potential confounding factors such as delivery mode, 21 , 34 39 antibiotic use, 15 , 18 and maternal obesity 22 , 26 , 40 . Infants exclusively breastfed have been shown to have a less diverse and rich intestinal microbiota in comparison to infants formula fed 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The mission of the Human Microbiome Project is to characterize the human microbiome from multiple body sites, but the investigators did not include human milk as one of the 18 anatomical regions or body sites of interest 9 . Nonetheless, independent studies have analyzed the human milk microbiota 3 , 6 , 7 , 10 26 . Early studies using cultured breast milk isolated only a limited number of genera 6 .…”
mentioning
confidence: 99%
“…Furthermore, it is possible that the overgrowth of one bacterial component over the others could lead to dysbiosis and pathologic states (such as in mastitis) [ 161 ]. In fact, during mastitic infection, it has been demonstrated that microbiome lose their diversity, with a predominance of bacterial pathogen species [ 162 ].…”
Section: Microbiomicsmentioning
confidence: 99%